Critical Care Nurses Competency Level on the Administration of Microinfusion Medication at Critical Care Unit Kenyatta National Hospital - Onwongá, Isaac Nyabuto; Inyama, Hannah; Rajula, Eve Risper (International Journal of Scientific Research and Management (IJSRM), 2020)
Background of the study: Most drugs given as Microinfusion require infusion pumps to administer. They are very potent with very narrow therapeutic index and any small changes on the process results in enormous effects to patients. The nursing profession has a duty to advocate for patients rights as well as do no harm. One of the core goals of nurses is medication administration; this puts nurses in the last line of defence against medication administration errors (MAEs). This study aimed to look into the roles played by nurse that hamper the efforts to reduce the Microinfusion MAEs on which minimal studies have been done.Objective: This study determined the competency level influencing the administration of Microinfusion medication by critical care nurses at Kenyatta National Hospital’s (KNH) Intensive Care Unit (ICU).Significance of study: Local data in the area of Microinfusion MAEs is not available, specifically KNH’s ICU. This study therefore sought to breech this gap and hopes to influence policy on management of critical patients, patient safety, environment, and curriculum development so as to reduce Microinfusion MAEs.Methodology: This study used a descriptive cross-sectional study design, simple random sampling was used to pick 64 participants. Quantitative data was analyzed by both descriptive and inferential statistics, which included regression analysis. Descriptive statistics were presented by use of the mean, percentages and standard deviation. Chi-square was used to determine statistical significance of the differences in proportions and logistic regression was used to identify factors that lead to Medication administration errors. Necessary ethical approval was sought.Results: The prevalence of MAEs was at 64.1% in the last six months, 65.6% 0f the respondents reported lack of supportive supervision, 37.5% of the respondents reported not to know mechanisms in place for reporting Microinfusion medication errors. This prevalence was of statistical significance when cross tabulated with critical care nurses competency level (p